دراسة أثرية لتمثال نذرى من أشمون محافظة المنوفية Archaeological Study of a Votive Statue from Ashmoun, Menoufia Governorate - Tamer Mohammed Fawzi Hussein Shafaa (Journal of General Union of Arab Archaeologists, 2022)
( Ar)يتناول هذا البحث نشر تمثالٍ من حجر الجرانيت الأسود، في حالة سيئة من الحفظ؛ نتيجة ما لحق به من تدمير في جزئه العلوى، بحيث لم يبق سوى الجزء السفلى منه, حيث يُظهر صاحبه جاثياً على ركبتيه يُقدم لفة من الحبال تُزين برأس الكبش رمز المعبود آمون-رع. وقد عُثر على هذا التمثال فى مدينة أشمون بمحافظة المنوفية، وهو محفوظ- حاليًا– بمتحف العريش القومي. تستهدف الدراسة نشر التمثال، ونسخ نصوصه الهيروغليفية وترجمتها، والتعليق الخطى واللغوي عليها، فضلًا عن توضيح قيمته التاريخية للإقليم الرابع من أقاليم مصر السفلى الذي كان يشغل أجزاء كبيرة من محافظة المنوفية، وكذلك قيمته الحضارية بما يحتوى عليه النقش من لقب يُشير إلى مكانة صاحبه الرفيعة في البلاط الملكى، هذا فضلاً عن قيمته الدينية بما يحمله من معان متعددة. ومما يؤسف له أن التمثال عُثر عليه مصادفة، وليس عن طريق حفائر أو مسح أثرى، ومن ثم غياب السياق الأثري، لذا يُثير هذا التمثال جملة من القضايا؛ كتحديد طرازه، ومصدره الأصلى وتاريخه، وعلى الرغم من هذه الإشكالات، فإن بعض الشواهد التقنية والفنية تُشير إلى أنه يرجع إلى عصر الدولة الحديثة؛ تحديداً عصر الأسرة الثامنة عشرة. ( en) This research deals with the publication of a black granite statue, in a poor condition; As a result of the destruction inflicted on its upper part, so that only the lower part remains, the owner is shown on his knees, holding surveyors cord adorned with the head of a ram, the symbol of the god Amun-Ra. which was found in Ashmoun Menoufia Governorate. Now, it is kept in the Arish National Museum. It the aim of this study is to publish, copy, translate and make comment on its hieroglyphic texts. It also aims at clarifying the historical value of the region the fourth, which used to occupy large parts of the Governorate of Menoufia, as well as its the cultural value, including important title indicating the high position of its owner in The royal court, in addition to its religious value, with its multiple meanings. Unfortunately, the statue was found by chance, and not by excavations or archaeological surveys, and thus became very problematic due to the absence of the archaeological context. So this statue raises a number of issues; Such as definition style, its original source and its history, even if these problems, there are some technical and artistic evidence indicates that it dates back to the New kingdom, specifically the Eighteenth Dynasty.